AZD5153, a Bivalent BRD4 Inhibitor, Suppresses Hepatocarcinogenesis by Altering BRD4 Chromosomal Landscape and Modulating the Transcriptome of HCC Cells - Lin, Cho-Hao; Kuo, Jimmy Chun-Tien; Li, Ding; Koenig, Aaron B.; Pan, Alexander; Yan, Pearlly; Bai, Xue-Feng; Lee, Robert J.; Ghoshal, Kalpana (Frontiers in Cell and Developmental Biology, 2022)
BRD4, a chromatin modifier frequently upregulated in a variety of neoplasms including hepatocellular cancer (HCC), promotes cancer cell growth by activating oncogenes through its interaction with acetylated histone tails of nucleosomes. Here, we determined the anti-HCC efficacy of AZD5153, a potent bivalent BRD4 inhibitor, and elucidated its underlying molecular mechanism of action. AZD5153 treatment inhibited HCC cell proliferation, clonogenic survival and induced apoptosis in HCC cells. In vivo, AZD5153-formulated lipid nanoemulsions inhibited both orthotopic and subcutaneous HCCLM3 xenograft growth in NSG mice. Mapping of BRD4- chromosomal targets by ChIP-seq analysis identified the occupancy of BRD4 with the promoters, gene bodies, and super-enhancers of both mRNA and noncoding RNA genes, which were disrupted upon AZD5153 treatment. RNA-seq analysis of polyadenylated RNAs showed several BRD4 target genes involved in DNA replication, cell proliferation, and anti-apoptosis were repressed in AZD5153-treated HCC cells. In addition to known tumor-promoting genes, e.g., c-MYC, YAP1, RAD51B, TRIB3, SLC17A9, JADE1, we found that NAPRT, encoding a key enzyme for NAD+ biosynthesis from nicotinic acid, was also suppressed in HCC cells by the BRD4 inhibitor. Interestingly, AZD5153 treatment upregulated NAMPT, whose product is the rate-limiting enzyme for NAD+ synthesis from nicotinamide. This may explain why AZD5153 acted in concert with FK866, a potent NAMPT inhibitor, in reducing HCC cell proliferation and clonogenic survival. In conclusion, our results identified novel targets of BRD4 in the HCCLM3 cell genome and demonstrated anti-HCC efficacy of AZD5153, which was potentiated in combination with an NAMPT inhibitor.